2017
DOI: 10.1038/srep45967
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlates of forgiving unintentional harms

Abstract: Mature moral judgments rely on the consideration of a perpetrator’s mental state as well as harmfulness of the outcomes produced. Prior work has focused primarily on the functional correlates of how intent information is neurally represented for moral judgments, but few studies have investigated whether individual differences in neuroanatomy can also explain variation in moral judgments. In the current study, we conducted voxel-based morphometry analyses to address this question. We found that local grey matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…In a first set of studies (1a-c), we observed that participants who self-reported to be more reflective and adept at cognitive deliberation by disposition were consistently more lenient in their judgments for accidental harms, as compared to participants who reported to rely more on the intuitive style of thinking. These results suggest that more capable reasoners (or reasoners more prone to engage in reflection) might solve the conflict posed by agentbased, intent-drive response to forgive (Patil, Calò, Fornasier, Young, et al, 2017;Young & Saxe, 2009) and victim-based, empathy-driven impulse to condemn (Patil, Calò, Fornasier, Cushman, et al, 2017) differently than less capable reasoners (or reasoners more prone to engage in intuition). Our second set of studies (2a-c), that relied on cognitive load manipulations from the dual-process toolbox (time pressure, interfering load, and mortality salience), showed no such compelling effects.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a first set of studies (1a-c), we observed that participants who self-reported to be more reflective and adept at cognitive deliberation by disposition were consistently more lenient in their judgments for accidental harms, as compared to participants who reported to rely more on the intuitive style of thinking. These results suggest that more capable reasoners (or reasoners more prone to engage in reflection) might solve the conflict posed by agentbased, intent-drive response to forgive (Patil, Calò, Fornasier, Young, et al, 2017;Young & Saxe, 2009) and victim-based, empathy-driven impulse to condemn (Patil, Calò, Fornasier, Cushman, et al, 2017) differently than less capable reasoners (or reasoners more prone to engage in intuition). Our second set of studies (2a-c), that relied on cognitive load manipulations from the dual-process toolbox (time pressure, interfering load, and mortality salience), showed no such compelling effects.…”
Section: Discussionmentioning
confidence: 83%
“…Accidental harms elicit a strong conflict in the observer because the two processes conflict with each other in terms of their output-the intent-based process focuses on innocent intentions of the actor and reduces severity of moral evaluations (Patil, Calò, Fornasier, Young, & Silani, 2017;Young & Saxe, 2009), while the outcome-based process localizes on empathic reaction towards the victim suffering and the agent's causal role in producing this outcome and increases severity of moral condemnation (Patil, Calò, Fornasier, Cushman, et al, 2017). Put differently, how we judge accidents depends on how we resolve the conflict posed by these two processes: difficulties in processing intentions leads to more punitive attitudes (e.g., autistic individuals, , while deficits in empathic reaction towards the victim can lead to forgiving attitudes (e.g., psychopathy and sadism , Trémolière & Djeriouat, 2016;Young, Koenigs, Kruepke, & Newman, 2012).…”
Section: Intention and Outcome In Moral Judgmentmentioning
confidence: 99%
“…In neurotypicals, moral judgment of an action is usually determined primarily by the agent’s intention rather than the outcome 13 . However, when intention and outcome are in conflict, moral judgments rely on the consideration of the agent’s mental state and the harmfulness of his doing 11 , 14 , 15 . Thus, when judging an action producing accidental harm (e.g., unintentionally hitting someone), individuals must weigh in the agent’s intention to override a preponderant negative response to the outcome 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Variables were demeaned, threshold-free cluster enhancement (TFCE) (Smith and Nichols, 2009) was applied and a variance smoothing parameter of 2 mm was used. In order to filter artifactual results, and increase the sensitivity, clusters containing less than 10 voxels were discarded, if present, following standard practice (Radua et al, 2012;Radua Joaquim et al, 2014;Patil et al, 2017;Tench et al, 2017).…”
Section: Methodsmentioning
confidence: 99%